2003
DOI: 10.1046/j.1460-9568.2003.02598.x
|View full text |Cite
|
Sign up to set email alerts
|

Calcium‐dependent phosphorylation processes control brain aromatase in quail

Abstract: Increased gene transcription activated by the binding of sex steroids to their cognate receptors is one important way in which oestrogen synthase (aromatase) activity is regulated in the brain. This control mechanism is relatively slow (hours to days) but recent data indicate that aromatase activity in quail preoptic-hypothalamic homogenates is also rapidly (within minutes) affected by exposure to conditions that enhance Ca2+-dependent protein phosphorylation. We demonstrate here that Ca2+-dependent phosphoryl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
174
0
2

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(189 citation statements)
references
References 64 publications
13
174
0
2
Order By: Relevance
“…Inhibition of these enzymes can be explained by either PLA2 activity or increased cytoplasmic calcium. For example, AA has been shown to inhibit 3␣-hydroxysteroid dehydrogenase (51), whereas an increase in calcium concentration has been shown to inhibit telomerase and aromatase (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of these enzymes can be explained by either PLA2 activity or increased cytoplasmic calcium. For example, AA has been shown to inhibit 3␣-hydroxysteroid dehydrogenase (51), whereas an increase in calcium concentration has been shown to inhibit telomerase and aromatase (52,53).…”
Section: Discussionmentioning
confidence: 99%
“…The rapid (MAPKindependent) effects of E2 on neural response properties are owed to its impact on the synaptic machinery (Tremere et al, 2009) and likely the fast regulation of aromatase activity. In fact, in NCM and other avian brain areas, aromatase is localized to presynaptic terminals and its activity is rapidly regulated by neuronal activity, in a calcium-dependent fashion (Balthazart et al, 2003;Peterson et al, 2005;Rohmann et al, 2007;Saldanha et al, 2011). These findings suggest that E2 operates more akin to a neuromodulator than a steroid hormone proper (Balthazart and Ball, 2006).…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…This inhibition is blocked by compounds chelating divalent ions such as EGTA and EDTA or by kinases inhibitors such as inhibitors of protein kinase A (PKA) or C (PKC) indicating that it is indeed caused by phosphorylation processes [16,18]. The identification of putative phosphorylation sites for PKC on the predicted quail aromatase sequence and westernblotting experiments on quail brain aromatase partially purified by immunoprecipitation confirmed that phosphorylation sites located on the aromatase protein itself are affected by the phosphorylating conditions that influence the enzymatic activity [18,19].…”
Section: Brain Synthesized Estrogensmentioning
confidence: 99%